Synthesis and Studies of 1,2-Dihydroquinoline Derivatives as Inhibitors of Lipid Peroxidation - Barta-Szalai, Gizella; Gere, Anikoó; Takács-Novák, Krisztina; Domány, György (Arzneimittelforschung, 2003)
A series of new spiro[naphto[2,1-c][2,7]naphtiridine-5,4’-piperidine] derivatives was prepared. Biochemical investigations revealed that all members of this series were potent inhibitors of both NADPH- and Fe2+-dependent lipid peroxidation (IC50< 10 µmol/l) in rat brain microsomes and rat brain homogenate, respectively.
Keywords: Antioxidants; Lipid peroxidation, inhibitors; Spiro[naphtho[2,1-c][2,7] naphtiridine-5,4’-piperidine]-derivatives; inhibition of lipid peroxidation, synthesis